The Effect of Bow Flare Angle Variation on Speed Boat Resistance - Sayyid Muhammad Al Ghofur; Arasy Fahruddin (National Research and Innovation Agency (BRIN Publishing), 2024)
The ship design industry today needs innovation, especially in terms of speed boat design, to improve efficiency and stability. The study aims to analyze the influence of the variation of the bow flare angle on the obstacles on the speed boat. Through numerical simulations using Maxsurf Resistance software and Savitsky Pre-Planing, Savitsky Planing, and Holtrop calculation methods, the study analyzed variations in bow flare angles of 25º, 30º, and 35º at speeds of 17, 19, and 21 knots. The simulation results showed that the 35º bow flare angle gives the lowest impediment of 34 kN and requires a power of 367,163 kW at a speed of 21 knots, making it a more efficient choice compared to the 25º and 30º angles which yield the highest impedance of 34.2 kN and requires 369,739 kW power. This analysis confirms that a larger bow flare angle can reduce barriers and improve energy efficiency, which is important for the design and operation of speed boats. These results show that choosing the right bow flare angle can improve ship speed efficiency by reducing obstacles and fuel consumption. The results of this research are expected to be beneficial to the designers and operators of speed boats in achieving optimal performance.